Անտիոքի գահաժառանգության խնդիրն ըստ Լևոն Ա Մեծագործի և Հռոմի Իննոկենտիոս III Պապի 1199 թ.նամակագրության - Տեր-Ղևոնդյան, Վահան; Թորոսյան, Վահե
Immediately after the proclamation of kingdom in Cilician Armenia (1198), the issue of the succession in Antiochia became the bone of contention between Levon I and the count of Tripoli Bohemund IV. The struggle lasted up to the year 1219 (the death of Armenian monarch) and it included both military and diplomatic confrontation. The two parties tried to attract to their side different powers – both external (the Roman Catholic Church, The Ayyubid “confederation”, especially The Sultanate of Aleppo, The Seljuks of Iconium etc.) and internal (local spiritual leaders, influential barons and especially the Templar and Hospitaller Knights). Сразу же после провозглашения королевства в Киликийской Армении (1198 г.) вопрос престолонаследия в Антиохийском княжестве стал яблоком раздора между Левоном I и графом Триполийским Боэмундом IV. Борьба между ними, длившаяся до 1219 г. (год кончины армянского монарха), включала в себя как военное, так и дипломатическое противостояние. Причем обе стороны старались привлечь, сделать своими союзниками как внешние политические силы (Римскую католическую церковь, “Конфедерацию” Аййубидов, и в первую очередь, соседний Алеппский султанат, Иконийских сельджуков и др.), так и внутриантиохийские (местных духовных предводителей, влиятельных баронов и конечно же военно-духовные ордены Тамплиеров и Госпитальеров).
Keywords: Կիլիկյան Հայաստան; Նամակագրություն